(untitled) (CIPEEX, 2025)
Non-steroidal anti-inflammatory drugs are a class of over-the-counter medicines used to relieve muscle pain, mild to moderate inflammation and fever. Because of their high efficacy and easy acquisition, they are widely consumed on a global scale. Even so, prolonged indiscriminate use is associated with a number of complications, affecting various organs and systems such as the kidneys, gastrointestinal tract and liver. This problem is associated with the practice of self-medication, i.e. the act of consuming medication by patients without the advice of a qualified health professional. This phenomenon is becoming a growing trend in many countries. The aim is to determine the significant role of pharmacists in preventing and controlling self-medication in the non-steroidal anti-inflammatory drug (NSAID) class. This study is an integrative bibliographic review, with a search for articles in the online databases Literatura Latino-Americana e do Caribe em Ciências da Saúde (Lilacs), Periódicos da CAPES, Biblioteca Virtual em Saúde (BVS), SciElo and National Library of Medicine (PubMed). Publications from 2020 to 2024 were included, and articles that were not published in Portuguese, English or Spanish were excluded. According to the analysis carried out, the harmful effects of NSAIDs are related to the lack of control due to the fact that they are easy to obtain and poorly monitored. The work of pharmacists is therefore essential, as they have extensive knowledge of medicines and direct access to the population, and can provide guidance and detect possible signs of complications caused by incorrect use of these medicines. Referências BUSTANJI, Yasser et al. Exploring the global landscape of self-medication among students: Trends, risks, and recommendations for safe and responsible practices. Pharmacy Practice, v. 22, n. 1, p. 1-14, 2024. CANDO, Verónica et al. USO RACIONAL DE ANTIINFLAMATORIOS NO ESTEROIDEOS EN EL HOSPITAL GENERAL ANDINO. Perfiles, Riobamba, v. 1, n. 30, p. 24-31, dic. 2023. GUEDES, Anne Caroline Santiago; ANDRADE, Leonardo Guimarães de. A ATUAÇÃO DO FARMACÊUTICO NO COMBATE A AUTOMEDICAÇÃO. Revista Ibero-Americana de Humanidades, Ciências e Educação, [S. l.], v. 7, n. 10, p. 1504–1514, 2021. DOI:10.51891/rease.v7i10.2677, 2021. ROMAINE, Adriane Pessoa; LOUREIRO, Fernanda Freire; DA SILVA, Francisca Vitória Menezes. Reações adversas no uso de Antiinflamatório não esteroidais (AINES) no Brasil: uma revisão sistemática Adverse reactions to nonsteroidal Anti-Inflammatory drugs (NSAIDS) in Brazil: a systematic review. Brazilian Journal of Development, v. 7, n. 6, p. 54653-54661, 2021. SANTOS, Adah Dandara Ferreira Oliveira et al. Intoxicação medicamentosa por AINES: uma revisão integrativa. Brazilian Journal of Health Review, v. 7, n. 4, p. e71066-e71066, 2024.